Spatial Information Theory
DOI: 10.1007/978-3-540-74788-8_24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Geometry, Landmarks and Orientation Strategies in the ‘Drop-Off’ Orientation Task

Abstract: Abstract. Previous work is reviewed and an experiment described to examine the spatial and strategic cognitive factors impacting on human orientation in the 'drop-off' static orientation scenario, where a person is matching a scene to a map to establish directional correspondence. The relative roles of salient landmarks and scene content and geometry, including space syntax isovist measures, are explored both in terms of general effects, individual differences between participant strategies, and the apparent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…More recently, Wiener and Franz (2004), showed that jaggedness, a measure resulting from the relation between an isovist's area and its perimeter, is related to people's perception of interestingness. Finally, Peebles, et al (2007) showed that isovist characteristics, in particular drift, were related to people's assessment of their sense of orientation in maps.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Wiener and Franz (2004), showed that jaggedness, a measure resulting from the relation between an isovist's area and its perimeter, is related to people's perception of interestingness. Finally, Peebles, et al (2007) showed that isovist characteristics, in particular drift, were related to people's assessment of their sense of orientation in maps.…”
Section: Discussionmentioning
confidence: 99%
“…self‐localization is a “more complex combined task […] which inevitably includes simultaneous orientation to some extent” (Peebles et al. , p. 391). Literature suggests that self‐localization is typically performed by “using local cues which are visible from our current location.…”
Section: Introductionmentioning
confidence: 99%
“…; Peebles et al. ), studies suggest that, “in geographically realistic contexts, visible salient landmarks bias people away from using optimal geometry‐matching strategies” (Davies and Peebles , p. 135). Achieving realism is one of the main goals of our experiments, therefore we focus in this article on orientation and self‐localization based on landmarks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other group of studies about landmark is for spatial ability in way finding (Cornell, Heth, & Skoczylas, 1999;Cubukcu & Nasar, 2005;Rossano, West, Robertson, Wayne, & Chase, 1999;Roger, Bonnardel, & Le Bigot, 2009), The ontology of landmark from various points like creating extensive spatial ability in way finding (Murrieta-Cid, Parra, & Devy, 2002;May & Ross, 2006;Peebles, Davies, & Mora, 2007), the value in helping orientation and navigation (Herzog & Leverich, 2003;Herzog & Kropscott, 2004;Klip-pel & Winter, 2005;Omer & Goldblatt, 2007;Caduff & Timpf, 2008).…”
Section: Methodsmentioning
confidence: 99%